(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Particular heat transfer coefficients of building elements gives quantitative notion only about heat losses through this building element. Analysis of the overall heat balance and heat losses of complete building and study of particular contribution of building elements in overall balance allows one to figure out the state of the building and find the building elements of bounding construction with most significant heat losses. Project variants of the buildings (or rebuilding in case of renovation), which ensure the desirable economy of energy and proportions of investments can be find varying the proportions of the surface area of building elements (e.g., windows and doors). A lot of factors can be included in requirements of heat consumption of the building. Moreover, monthly calculations are possible. These both aspects contribute in so called method of full calculations, which is made in correspondence with standard EN 832. Though, it is possible to use also the simplified variant of calculations offered by Latvian building normative LBN 002-01. Both approaches of modelling are realised in elaborated software HeatMod, which is made in laboratory of MMTEP. Both methodologies are applicable to buildings, which can be divided in separate blocks in such a way that temperature in each of blocks is approximately constant or exists different number of floors in each of blocks. Separate analysis of heat balance is made for each block and finally the obtained heat consumptions are summed together. This allows one to consider really existing temperature difference in building, e.g., in office and depository. It is possible to approximate also the influence of given regime of temperature. The possibility to minimise heat losses and their contributions are analysed on particular examples. Comparative analysis of both methods is performed and the dependence of various heat transfers on the change of different input data are studied.